BOOK REVIEWS (Journal of Finance, 1975)
Book reviewed in this article: Returns in Over‐the‐Counter Stock Markets . By P aul F. J essup and R oger B. U pson Financial Management . By R obert M. S oldofsky and G arnet D. O live European Monetary Unification and Its Meaning for the United States . L awrence B. K rause and W alter S. S alant Problems of a World Monetary Order . By G erald M. M eier International Monetary Reconstruction . By W ilbur F. M onroe . Foreign Dollar Balances and the International Role of the Dollar . By R aymond R. M ikesell and J. H erbert F urth . Who Bears the Tax Burden . By J oseph A. P echman and B enjamin A. O kner The Postwar Canadian Housing and Residential and Mortgage Markets and the Role of Government . By L awrence B erk S mith Real Estate Appraisal: Review and Outlook . By P aul F. W endt Real Estate Finance . By J ohn B. W iedemer Macroeconomics: A Neoclassical Introduction . By M erton H. M iller and C harles W. U pton